SYNTHESIS AND STRUCTURE OF THE COMPLEX OF NICKEL(II) ACETATE AND SODIUM SALT OF SUCCINCIC ACID (Scientific journal of the Fergana State University, 2024)
This article highlights the research results on the synthesize of a new heterometallic complex compound of nickel(II) acetate and succinic acid with the sodium salt and the determination of their composition, structure and properties by physico-chemical methods: scanning electron microscope-energy dispersive analysis (SEM-EDT), X-ray phase analysis, thermal analysis and X-ray structural analysis. The central atom of the complex compound is nickel, the oxygen atom of the carboxyl group of the acetate residue and the sodium salt of succinic acid are interconnected through the oxygen atom of the carboxyl group, forming a complex compound with a coordination number of 6.